2017
DOI: 10.1017/s0967199416000459
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of sperm media with zinc, D-aspartate and co-enzyme Q10 protects bull sperm against exogenous oxidative stress and improves their ability to support embryo development

Abstract: High levels of reactive oxygen species in the semen of infertile patients or spontaneously generated during in vitro sperm handling may impair sperm quality, fertilization and embryo developmental competence. We recently reported that zinc, d-aspartate and co-enzyme Q10, contained in the dietary supplement Genadis® (Merck Serono), have protective effects on human and bull sperm motility, lipid peroxidation and DNA fragmentation in vitro; furthermore, in bovine, treated spermatozoa had an improved ability to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
(48 reference statements)
0
26
0
Order By: Relevance
“…The quality of semen is often reduced after semen collection and cryopreservation due to oxidative stress. Impact of oxidative stress in reducing sperm quality has been reported in human (Saleh et al, 2003), rat (Chitra et al, 2003) horse (Ball et al, 2008), and bovine (Barbato et al, 2017). These results show that the basic components in semen extender is not sufficient to protect sperms from oxidative damage.…”
Section: Introductionmentioning
confidence: 95%
“…The quality of semen is often reduced after semen collection and cryopreservation due to oxidative stress. Impact of oxidative stress in reducing sperm quality has been reported in human (Saleh et al, 2003), rat (Chitra et al, 2003) horse (Ball et al, 2008), and bovine (Barbato et al, 2017). These results show that the basic components in semen extender is not sufficient to protect sperms from oxidative damage.…”
Section: Introductionmentioning
confidence: 95%
“…Over the last decade, different studies have aimed at determining the clinical effects of low sperm quality upon ART outcomes, both in humans [16][17][18] and animals [19,20]. This research has demonstrated that low sperm motility and high sperm DNA fragmentation have a detrimental impact on natural fertility, reducing pregnancy achievement and increasing pregnancy loss [16,21,22]. Despite this clear consensus about the negative effects of sperm quality on natural fertility, studies analyzing the male factor influence on IVF and ICSI outcomes in humans have reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is difficult to establish which percentages of infertile patients have an underlying mechanism of oxidative stress, it is known that it could be present as a factor in asthenozoospermic, teratozospermic, and oligozoospermic patients who present reproductive issues [77,78]. All these parameters have been associated in different studies with a reduction in natural pregnancy, both in animal [79,80] and human studies [76,81,82], supporting the evidence that oxidative stress leads to a reduction in natural fertility rates [77,83].…”
Section: Natural Pregnancymentioning
confidence: 80%